Using of germinated seeds and grains in the technology of functional biscuits - Yasinska, Iryna; Ivanova, Victoria (My University, 2018)
Studies have shown that the use of supplements from germinated seeds allows not only increasing the nutritional value of traditional products, but also to gives them new flavoring shades. In high-fat foods recipes, the use of such supplements is an effective method for preventing fat oxidation due to the high content of antioxidants.
Keywords: кафедра технології оздоровчих продуктів; germination; funcional biscuits; пророщування; печиво функціонального призначення